Stensvold, Anne, ed. 2021. "Blasphemies Compared. Transgressive Speech in a Globalized World" - Andrea Rota (DIN)
[AI generated] Andrea Rota reviews Blasphemies Compared, edited by Anne Stensvold, highlighting its global and interdisciplinary approach to understanding blasphemy. The volume includes 17 chapters exploring blasphemy as a dynamic, transhistorical phenomenon shaped by legal, political, and cultural contexts. Contributors analyze theoretical definitions, cross-cultural semantics, and case studies from Europe, Asia, and the Middle East. Central themes include the politicization of blasphemy, the blurred boundaries between religion and secularism, and the role of media in constructing offense. Rota praises the volume’s depth and scope while noting challenges in comparison. The book invites reflection on power, identity, and the sacred in globalized societies.